2020
DOI: 10.1038/s41431-020-0632-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide

Abstract: Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

7
0

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Taken together with population data, these AOH data from ES suggest that TNNT3 : c.481-1G>A may represent a Clan Genomics derived founder mutation in the Latino population. 10 , 11 The nucleotide is well conserved ( figure 2B ), and the variant is predicted damaging by multiple variant annotation tools (MutationTaster: Disease causing; CADD score: 33) and splicing predictors ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Taken together with population data, these AOH data from ES suggest that TNNT3 : c.481-1G>A may represent a Clan Genomics derived founder mutation in the Latino population. 10 , 11 The nucleotide is well conserved ( figure 2B ), and the variant is predicted damaging by multiple variant annotation tools (MutationTaster: Disease causing; CADD score: 33) and splicing predictors ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, both frameshift mutations, c.1684delC and c.1794delC, occur in runs of 5C and 3C nucleotides, respectively. These mutations likely occurred de novo in a distant member of the clan by slippage during DNA replication and were homozygozed by identity‐by‐descent in the family given consanguinity (Bi et al, 2006; Gonzaga‐Jauregui et al, 2020; Lupski et al, 2011). All three mutant mRNAs, the two reported by Monies et al and the one reported herein, likely escape NMD and thus make a protein mutated at the carboxy‐terminus that may cause LoF by acting as either a null or hypomorphic allele.…”
Section: Discussionmentioning
confidence: 99%
“…shinyapps.io/nmdescpredictor/)(Coban-Akdemir et al, 2018). To quantitate degree of consanguinity and delineate potential identity-by-decent (IBD) intervals, unphased ES data were analyzed using BafCalculator (https://github.com/BCM-Lupskilab/BafCalculator) according to the BafCalculator algorithm described previously(Gambin et al, 2017;Gonzaga-Jauregui et al, 2020). The variant was located within 10.6 and 10.8 Mb intervals of absence of heterozygosity (AOH) blocks with a total genome-wide AOH size of 401.74 and 287.24 Mb in the proband (BAB13277) and affected sister (BAB13280), respectively (Figure1(d)).4 | DISCUSSIONWe report a family from Egypt with a novel homozygous frame-shift variant c.1684delC p.(Arg562Alafs*56) in the last coding exon of ALKBH8.…”
mentioning
confidence: 99%
“…Disease causing variants with such high allele frequencies tend to be found in established recessive disorders, often attributed to founder mutation alleles. 4 In contrast, if a yet-to-be- defined recessive disease trait gene does not have pathogenic alleles represented at a sufficient population frequency, disease discovery and annotation of the gene would be greatly hampered due to the extremely low incidence and difficulty in ascertaining affected individuals, even when considering a world-wide population of 7.8 billion. An exception to this rule occurs when disease gene discovery research is conducted in populations with an elevated coefficient of consanguinity and autozygosity.…”
Section: Introductionmentioning
confidence: 99%
“…In this circumstance, the allele pool shrinks to the Clan of the patient’s extended family, which dramatically escalates the effective disease-allele frequency. 4 ; 5 Thus, the probability of ascertaining patients with the recessive disorder increases exponentially, even when all existing alleles are ultra-rare in sampling the general population. 6…”
Section: Introductionmentioning
confidence: 99%